2017
DOI: 10.5194/se-8-921-2017
|View full text |Cite
|
Sign up to set email alerts
|

Flexible parallel implicit modelling of coupled thermal–hydraulic–mechanical processes in fractured rocks

Abstract: Abstract. Theory and numerical implementation describing groundwater flow and the transport of heat and solute mass in fully saturated fractured rocks with elasto-plastic mechanical feedbacks are developed. In our formulation, fractures are considered as being of lower dimension than the hosting deformable porous rock and we consider their hydraulic and mechanical apertures as scaling parameters to ensure continuous exchange of fluid mass and energy within the fracturesolid matrix system. The coupled system of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 42 publications
0
54
0
Order By: Relevance
“…To simulate the coupled transport of heat and fluid, we use the open-source software GOLEM [60]. Golem is a flexible, parallel scalable finite elementbased simulator for thermo-hydro-mechanical process modelling in fractured porous rocks as based on the MOOSE framework [61].…”
Section: Numerical Simulationmentioning
confidence: 99%
“…To simulate the coupled transport of heat and fluid, we use the open-source software GOLEM [60]. Golem is a flexible, parallel scalable finite elementbased simulator for thermo-hydro-mechanical process modelling in fractured porous rocks as based on the MOOSE framework [61].…”
Section: Numerical Simulationmentioning
confidence: 99%
“…In this study we rely on the GOLEM simulator (Cacace and Jacquey, 2017) that builds on the flexible, object oriented MOOSE framework (Gaston et al, 2009). Using this approach, fractures are considered as being of lower dimension (2D structures) than the hosting deformable 3D porous rock and their hydraulic aperture is then used as scaling parameter to ensure continuous exchange of fluid mass and energy within the fracture-solid matrix system (Cacace and Jacquey, 2017). In what follows, the governing equations of groundwater flow, heat transport and rock deformation are briefly described, more information on their numerical implementation is provided in Cacace and Jacquey (2017).…”
Section: Insert Table 1 Here 3 Methodsmentioning
confidence: 99%
“…Sensitivity studies have shown that such effects would influence the absolute values of temperatures but not their regional distribution pattern (Majorowicz and Wybraniec, 2011). Neglecting the influence of coupled fluid and heat transport may also lead to erroneous conclusions as the conductive thermal model that best reproduces the observed heat flow considers an "effective" thermal conductivity that contains the superposed effects of different heat transport processes (Cacace et al, 2010). Again, local studies would be required to better quantify the absolute impact of this simplification.…”
Section: Model Limitationsmentioning
confidence: 99%
“…For regional exploration, complementary workflows use integrated 3-D structural and physics-based models that help to predict the temperature distribution in the subsurface by taking into account the heterogeneous structural configuration as well as the, often non-linear, causative processes (e.g. Cacace et al, 2010;.…”
Section: Introductionmentioning
confidence: 99%